2018
DOI: 10.1016/j.heares.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The use of ecological momentary assessment in hearing research and future clinical applications

Abstract: To obtain real-world insights into the hearing difficulties of individuals, the field of hearing research has recently started to adopt ecological momentary assessment. Using this approach, study participants describe their experiences in real time, in their own natural environment. This paper describes the use of ecological momentary assessment in hearing research to date. Several studies have shown the approach is feasible and has good construct validity for use with adults with hearing impairment and/or tin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
(53 reference statements)
0
20
1
Order By: Relevance
“…The compliance rate reported in this study is higher than that reported in a systematic review of EMA studies with youths, where event-based triggered studies reported compliance to be between 47.9% and 74.1% (Heron et al 2017). In a summary of EMA studies from Timmer, Hickson, and Launer (2018b) compliance amongst adult hearing aid users ranged between 77% and 93%. Overall, the children in this study reported a high level of enthusiasm around the use of mobile technology to inform the hearing aid fitting process.…”
Section: Discussioncontrasting
confidence: 76%
“…The compliance rate reported in this study is higher than that reported in a systematic review of EMA studies with youths, where event-based triggered studies reported compliance to be between 47.9% and 74.1% (Heron et al 2017). In a summary of EMA studies from Timmer, Hickson, and Launer (2018b) compliance amongst adult hearing aid users ranged between 77% and 93%. Overall, the children in this study reported a high level of enthusiasm around the use of mobile technology to inform the hearing aid fitting process.…”
Section: Discussioncontrasting
confidence: 76%
“…Second, patients can struggle to accurately describe listening problems retrospectively. 11 If there is a lengthy delay between their experience of a problem and a visit to their provider, key details about the problem may be forgotten. Third, hearing aids are typically fine-tuned in the clinic, with the patient expected to rapidly assess whether the new, fine-tuned settings have adequately addressed the problem.…”
mentioning
confidence: 99%
“…Ecological momentary assessment is interesting in a world where ubiquitous technology is increasingly following us, quantifying, tracking, and even pre-empting our behaviors and thoughts. The convergence of PROMs with hearing device usage, acoustic environments, and health and wellbeing data provides a holistic view of a patient’s level of functioning against the context and environment in which they evolve ( Timmer et al, 2018 ). Cloud-based programming of hearing devices also calls for PROMs that are easier and closer to the patient so that replacing face-to-face appointments with remote care does not have to compromise opportunities for outcome measures.…”
Section: Anticipated Results and Discussionmentioning
confidence: 99%